Muatan Pendidikan Holistik dalam Kurikulum Pendidikan Dasar dan Menengah - Herry Widyastono (Badan Standar, Kurikulum, dan Asesmen Pendidikan, Kemendikbudristek, 2012)
Holistic education is the education which develops all students potentials in harmony comprises intellectual, emotional, physical, social, esthetic, and spiritual potentials. This article is aimed at describing on whether or not there is the degree of holistic approach in education, particularly for the basic and secondary education. In addition, this describes its implementation at the schools within the basic and secondary education. The problems are formulated as follows 1) whether the basic and secondary education has already been regarded as holistic education?, 2) if yes, how its implementation at the schools concerned. This concludes that: 1) the basic and secondary curriculums have, in principle, been as holistic ones because its principles, reference, and procedure to develop the curriculum are in line with the definition, objective, and the principles which support to it. 2) The holistic education is not yet implemented comprehensivelyat the schools. In terms of its implementation it is, therefore, advisable that all teachers, while teaching in the classroom, should give the students to have ample opportunities to develop not only their cognitive domain, but their psychomotor and affective ones through active learning. ABSTRAK Pendidikan holistik merupakan pendidikan yang mengembangkan seluruh potensi siswa secara harmonis, meliputi potensi intelektual, emosional, phisik, sosial, estetika, dan spiritual. Kajian ini bertujuan untuk memberikan gambaran tentang ada tidaknya muatan pendidikan holistik dalam kurikulum pendidikan dasar dan menengah. Selain itu juga memberikan gambaran tentang implementasi pendidikan holistik dalam pembelajaran di pendidikan dasar dan menengah. Permasalahan dirumuskan sebagai berikut: 1) Apakah kurikulum pendidikan dasar dan menengah sudah memuat pendidikan holistik? 2) Bila sudah, bagaimana implementasi pendidikan holistik dalam pembelajaran? Kajian menyimpulkan bahwa: 1) Dokumen kurikulum pendidikan dasar dan menengah pada hakikatnya sudah memuat pendidikan holistik, karena prinsip, acuan, dan prosedur pengembangan kurikulum sejalan dengan pengertian, tujuan, dan prinsip pendidikan holistik; 2) Pendidikan holistik belum diimplementasikan secara komprehensif dalam pembelajaran. Dalam rangka mengimplementasikan pendidikan holistik dalam pembelajaran, direkomendasikan agar guru dalam melaksanakan pembelajaran tidak hanya mengembangkan ranah pengetahuan, melainkan juga ranah keterampilan dan sikap, melalui pendekatan belajar siswa aktif.